Anish Kapoor : shooting into the corner - Noever, Peter; Acconci, Vito; Busse, Bettina M. (Ostfildern : Hatje Cantz, 2009)
- What is this all about? / Peter Noever -## Wax works 1992-2008 -## Viewing ghost / Michael Stavaric -## Works on paper 1987-2008 -## Aggression and beauty / Bettina M. Busse -## MAK 2009 : shooting into the corner -## Notes for Kapoor at MAK / Vito Acconci -## In the end was the vaseline : on Anish Kapoor's shooting "Beyond the pleasure principle" / Gabriel Ramin Schor -## Kapoor and the sublimity problem of today / Burghart Schmidt -## Anish Kapoor and the subversion of the object : and a few remarks on the art of shooting a sculpture / August Ruhs.
Publ. n.a.v. de tentoonstelling te Wenen (MAK) van 21 jan. tot 19 april 2009
boek
Keywords: Kapoor, Anish